Analisis Kualitas Suara Dalam Komunikasi Antar IP Phone Pada Jaringan Intranet di Politeknik Negeri Malang - Arlisa Krisna; Martono Dwi Atmadja; Farida Arinie Soelistianto (Jurnal Jaringan Telekomunikasi, 2022)
IP Phone is a Voice over Internet Protocol (VoIP) device that can transmit voice using IP. From communication between IP Phones there are waveforms of input and output information signals, the response of voice amplitude to changes in voice frequency and delay value from time shift at the beginning of the wave period of the input and output information signal using the Transmission Test Set and Oscilloscope measuring instruments to determine the character of the sound quality in communication between IP Phones according to the parameter test results. The system test results are that the waveform of the input and output information signal at the sound frequency has a sine wave shape. However, the output waveform of IP Phone A with a frequency of 300Hz to 1100Hz and IP Phone B with a frequency of 300Hz to 1300Hz is distorted, then from the results of the Peak to Peak wave is known to have a voltage gain, that is, the greater the frequency value at the input, the smaller the value of the resulting voltage gain.